What kind of financial mathematics should be taught math classes? TSG 23: Mathematical literacy (R&E-SOURCE, 2017)
A qualitative approach via fundamental ideas yields an argumentation for establishing financial mathematical topics in math classes. Such ideas and their relevance for classes will be discussed in advanced.